Composite positive electrode material and preparation method and application thereof

CN123017929APending Publication Date: 2026-10-30JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611207502.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但这种做法的局限性也很明显,这种包覆层无法随颗粒体积变化而动态适应,一旦循环产生微裂纹,它既不能自主修复,也无法清除已经生成的微量气体

Benefits of technology

在本申请所提供的聚合物层中,化合物A中的氨基能够主动捕获正极表面可能释放的CO2,有助于减轻界面气体积累带来的负面影响;同时,化合物A中的亚胺键的可逆动态特性赋予包覆层具备一定的自修复能力,可在循环应力作用下对微损伤进行一定程度的修复。两者共存于同一包覆层,在抑制副反应与维持界面接触方面形成有益互补,从而有利于提升复合正极材料在长期循环中的结构完整性和电化学稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017929A_ABST
    Figure CN123017929A_ABST
Patent Text Reader

Abstract

The application provides a composite positive electrode material and a preparation method and application thereof. The composite positive electrode material comprises a positive electrode material and a polymer layer coated on the surface of the positive electrode material, and the polymer layer comprises a compound A containing an imine bond and an amino group. In the polymer layer provided by the application, the amino group in the compound A can actively capture CO2 that may be released from the surface of the positive electrode, thereby helping to reduce the negative effects caused by the accumulation of interface gas. Meanwhile, the reversible dynamic characteristics of the imine bond in the compound A endow the coating layer with a certain self-repairing ability, which can repair the micro-damage to a certain extent under the action of cyclic stress. Both of them coexist in the same coating layer, which forms a beneficial complementation in inhibiting side reactions and maintaining interface contact, thereby being beneficial to improving the structural integrity and electrochemical stability of the composite positive electrode material in long-term cycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of batteries, and in particular relates to a composite cathode material, its preparation method and application. Background Technology

[0002] All-solid-state batteries use non-flammable solid electrolytes (sulfides, oxides, or halides) instead of traditional liquid electrolytes, theoretically offering both high energy density and high safety. However, interfacial side reactions between the high-voltage cathode (such as nickel-cobalt-manganese ternary, lithium cobalt oxide, or lithium-rich manganese-based materials) and the solid electrolyte limit the electrochemical performance of all-solid-state batteries. For example, alkaline substances (such as Li₂CO₃ and LiOH) remaining on the cathode surface can react with the electrolyte or conductive agent to release CO₂; simultaneously, the volume expansion and contraction of particles during cycling can cause the interfacial contact to gradually fail, exposing fresh reaction surfaces and thus continuously generating gas.

[0003] To address the aforementioned technical issues, the current mainstream optimization strategy involves coating the cathode material with oxides, phosphates, or fluorides, using an inert protective layer to physically isolate the cathode from direct contact with the electrolyte, thereby delaying side reactions to some extent. However, this approach also has obvious limitations. This coating layer cannot dynamically adapt to changes in particle volume, and once microcracks develop during cycling, it cannot self-repair nor remove the trace amounts of gas that have already been generated. Summary of the Invention

[0004] In view of this, this application aims to provide a composite cathode material, its preparation method and application, so as to improve the cycle life and safety performance of batteries.

[0005] To solve the above-mentioned technical problems, this application is implemented as follows: According to a first aspect of this application, this application provides a composite cathode material comprising a cathode material and a polymer layer coating its surface, the polymer layer comprising a compound A containing both imine bonds and amino groups.

[0006] Preferably, compound A also includes borate ester bonds.

[0007] Preferably, compound A is a compound as shown in formula (I); Formula (1) Wherein, A1 is selected from substituted or unsubstituted phenyl groups, and when the phenyl group is substituted, the substituent is selected from at least one of C1-4 alkyl, phenyl, aminophenyl, hydroxyl, and halogen; A2 is selected from substituted or unsubstituted phenyl groups, and when the phenyl group is substituted, the substituent is selected from at least one of halogen, hydroxyl, C1-4 alkyl or haloalkyl, C1-4 alkenyl, C1-4 alkynyl, and C1-4 aldehyde; R1, R2, R3, R4, and R5 are each independently selected from one of hydrogen atom, amino, hydroxyl, aldehyde, and the group shown in formula (II), and at least one of R1 and R2 contains an amino group; in the group shown in formula (II), Indicates a linking bond; R6 and R7 are each independently selected from one of substituted or unsubstituted C3-6 cycloalkyl, substituted or unsubstituted C1-8 alkoxy, or substituted or unsubstituted C1-8 alkyl. When the cycloalkyl, alkoxy, or alkyl is substituted, the substituent is each independently selected from at least one of carbonyl, ester, or C1-3 alkyl. R8 and R9 are each independently selected from one of hydrogen atom or substituted or unsubstituted C1-8 alkyl.

[0008] Formula (II) Preferably, the polymer layer further includes compound B as shown in formula (iii), containing boron-oxygen-boron bonds, wherein R 10 R 11 R 12 R 13 Each substituent is independently selected from one of substituted or unsubstituted C3-6 cycloalkyl, substituted or unsubstituted C1-8 alkoxy, or substituted or unsubstituted C1-8 alkyl; when the cycloalkyl, alkoxy, or alkyl is substituted, the substituent is independently selected from at least one of carbonyl, ester, or C1-3 alkyl.

[0009] Formula (3) Preferably, the cathode material includes a nickel-containing material with the chemical formula LiNi. x Co y M 1-x-y O2; wherein M is one or more of Li, Na, B, Mg, Al, Ni, Fe, Mn, K, Ca, Co, V, Cr, Cu, Zn, Zr, Nb, Sr, Sn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; 0.8 <x<1,0<y<0.2,0<z<0.2。

[0010] Preferably, the D50 of the positive electrode material is 3μm~6μm.

[0011] According to a second aspect of this application, this application provides a method for preparing the composite cathode material as described above. The method includes the following steps: mixing borate ester monomers, aldehyde monomers, and amine monomers to obtain a mixed solution; adding the cathode material that has undergone plasma treatment to the mixed solution to carry out an in-situ polymerization reaction to form a polymer layer on the surface of the cathode material, thereby obtaining the composite cathode material.

[0012] Preferably, the borate ester monomer includes at least one of 5,5-dimethyl-1,3,2-dioxoboronylcyclopentane, MIDA cyclobutylboronic acid ester, and pinacol ester borate.

[0013] Preferably, the aldehyde monomer includes at least one of terephthalaldehyde, 2,3,5,6-tetrafluoroterephthalaldehyde, 1,3,5-tricarboxyloylphloroglucinol, 2,5-diethoxyterephthalaldehyde, 2,5-dipropynoxyterephthalaldehyde, 2,4-dihydroxy-1,3,5-benzenetrialdehyde, and 2,5-dihydroxyterephthalaldehyde.

[0014] Preferably, the amine monomer includes at least one of 1,3,5-tris(4-aminophenyl)benzene, 1,3,5-tris(4-aminomethylphenyl)benzene, and p-phenylenediamine.

[0015] Preferably, the amount of borate ester monomer added is 2.0 wt% to 4.0 wt% of the cathode material.

[0016] Preferably, the amount of aldehyde monomer added is 3.0wt% to 5.5wt% of the mass of the cathode material.

[0017] Preferably, the amount of amine monomer added is 3.5wt% to 6.0wt% of the mass of the cathode material.

[0018] Preferably, the mixture also includes at least one of a reaction catalyst and a conductive agent.

[0019] Preferably, the reaction catalyst includes at least one of LiTFSI, LiClO4, and LiBOB. Preferably, the conductive agent includes at least one of PEDOT-LLTO nanowires, PEDOT:PSS, single-walled carbon nanotubes, and carbon nanofibers.

[0020] Preferably, the amount of reaction catalyst added is 0.5wt% to 2.5wt% of the mass of the positive electrode material. Preferably, the amount of conductive agent added is 1.0wt% to 4.0wt% of the mass of the positive electrode material.

[0021] Preferably, the reaction conditions for the in-situ polymerization reaction are 40°C to 80°C for 1 to 3 hours.

[0022] Preferably, the plasma used in the plasma treatment includes oxygen plasma.

[0023] Preferably, after in-situ polymerization, a slurry is obtained and then subjected to microwave treatment.

[0024] Preferably, the microwave treatment reaction conditions are as follows: in an inert gas atmosphere, microwave power of 150W~350W, reaction temperature of 120℃~180℃, and time of 5 minutes~15 minutes.

[0025] According to a third aspect of this application, this application provides a battery comprising the composite positive electrode material as described above, or the composite positive electrode material prepared by the method described above.

[0026] The technical solution of this application has at least the following beneficial effects: In the polymer layer provided in this application, the amino groups in compound A can actively capture CO2 that may be released from the cathode surface, helping to mitigate the negative impact of interfacial gas accumulation. Simultaneously, the reversible dynamic properties of the imine bonds in compound A endow the coating layer with a certain degree of self-healing capability, allowing it to repair micro-damage to some extent under cyclic stress. The coexistence of these two elements in the same coating layer creates a beneficial complementarity in suppressing side reactions and maintaining interfacial contact, thereby improving the structural integrity and electrochemical stability of the composite cathode material during long-term cycling.

[0027] Other features and advantages of this application will be described in detail in the following detailed description section. Attached Figure Description

[0028] Figure 1 This is a schematic diagram of the mechanism of the composite cathode material provided in this application; Among them, 1. cathode material; 2. cathode material; 3. interface modification layer; Figure 2 This is a high-resolution transmission electron microscope image provided in Embodiment 1 of this application. Detailed Implementation

[0029] This application discloses a composite cathode material, its preparation method, and its application. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this application. The methods and applications of this application have been described through preferred embodiments. Those skilled in the art can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this application to realize and apply the technology of this application.

[0030] In the description of this application, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0031] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges, or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. Unless otherwise stated, all embodiments and optional embodiments of this application can be combined with each other to form new technical solutions.

[0032] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0033] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0034] To improve the cycle life and safety performance of batteries, this application provides a composite cathode material, its preparation method, and its application.

[0035] According to a first aspect of this application, this application provides a composite cathode material comprising a cathode material and a polymer layer coating its surface, the polymer layer comprising a compound A containing both imine bonds and amino groups.

[0036] In the polymer layer provided in this application, the amino group in compound A can actively capture CO2 generated on the cathode surface due to carbonate decomposition, effectively inhibiting subsequent side reactions between CO2 and the electrolyte or cathode interface, thereby reducing the generation of insulating byproducts (such as Li2CO3), which helps maintain the unobstructed ion transport channels, alleviates the increase in interfacial impedance, and thus slows down capacity decay. Simultaneously, the reversible dynamic characteristics of the imine bond give the coating layer a certain self-healing ability during cycling, enabling it to adapt to particle volume changes and repair microcracks, maintaining the integrity of the interfacial contact. The synergistic effect of these two factors reduces the cumulative impact of harmful gases at the source and enhances the durability of the coating layer structurally, thus improving the capacity retention and cycle stability of the composite cathode material during long-term charge-discharge processes.

[0037] In one embodiment of this application, compound A further includes a borate ester bond.

[0038] Compound A in the polymer layer further introduces borate ester bonds, resulting in a coating layer with both imine and borate ester bonds, forming two types of dynamic covalent cross-linked structures. The imine bonds themselves impart a certain self-healing response capability to the coating layer, while the introduction of borate ester bonds further enriches the dynamic cross-linked network. The synergy between these two factors helps improve the self-healing efficiency of the coating layer in response to volume changes and microcracks during cycling, thereby maintaining the integrity of the interfacial structure and the density of the coating layer for a longer period. This is beneficial for maintaining the capacity stability of the composite cathode material during long-term charge-discharge processes.

[0039] In one embodiment of this application, compound A is a compound as shown in formula (a); Formula (1) Wherein, A1 is selected from substituted or unsubstituted phenyl groups, and when the phenyl group is substituted, the substituent is selected from at least one of C1-4 alkyl, phenyl, aminophenyl, hydroxyl, and halogen; A2 is selected from substituted or unsubstituted phenyl groups, and when the phenyl group is substituted, the substituent is selected from at least one of halogen, hydroxyl, C1-4 alkyl or haloalkyl, C1-4 alkenyl, C1-4 alkynyl, and C1-4 aldehyde; R1, R2, R3, R4, and R5 are each independently selected from one of hydrogen atom, amino, hydroxyl, aldehyde, and the group shown in formula (II), and at least one of R1 and R2 contains an amino group; in the group shown in formula (II), Indicates a linking bond; R6 and R7 are each independently selected from one of substituted or unsubstituted C3-6 cycloalkyl, substituted or unsubstituted C1-8 alkoxy, or substituted or unsubstituted C1-8 alkyl. When the cycloalkyl, alkoxy, or alkyl is substituted, the substituent is each independently selected from at least one of carbonyl, ester, or C1-3 alkyl. R8 and R9 are each independently selected from one of hydrogen atom or substituted or unsubstituted C1-8 alkyl.

[0040] Formula (II) In one embodiment of this application, the polymer layer further includes compound B as shown in formula (iii), containing boron-oxygen-boron bonds, wherein R 10 R 11 R 12 R 13 Each substituent is independently selected from one of substituted or unsubstituted C3-6 cycloalkyl, substituted or unsubstituted C1-8 alkoxy, or substituted or unsubstituted C1-8 alkyl; when the cycloalkyl, alkoxy, or alkyl is substituted, the substituent is independently selected from at least one of carbonyl, ester, or C1-3 alkyl.

[0041] Formula (3) The polymer layer provided in this application also contains compound B, whose boron-oxygen-boron (BOB) dynamic covalent bonds in its molecular structure can undergo reversible breakage and recombination under suitable temperature or mechanical force. This characteristic can further optimize the active response of the coating layer to particle volume changes and interfacial stress during charge-discharge cycles, and promptly repair microcracks through the reconstruction of the bonding network, which is conducive to maintaining the structural integrity of the coating layer for a longer period of time, thereby further improving the capacity retention capability of the composite cathode material during long-term cycling.

[0042] In one embodiment of this application, the positive electrode material includes a nickel-containing material, the chemical formula of which is LiNi. x Co y M 1-x-y O2; wherein M is one or more of Li, Na, B, Mg, Al, Ni, Fe, Mn, K, Ca, Co, V, Cr, Cu, Zn, Zr, Nb, Sr, Sn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; 0.8 <x<1,0<y<0.2,0<z<0.2。

[0043] In one embodiment of this application, the D50 of the positive electrode material is 3μm to 6μm.

[0044] In one embodiment of this application, the cathode material includes one of single crystal, quasi-single crystal, and polycrystalline.

[0045] In one embodiment of this application, the thickness of the polymer layer is 2nm to 5nm.

[0046] According to a second aspect of this application, this application provides a method for preparing the composite cathode material as described above. The method includes the following steps: mixing borate ester monomers, aldehyde monomers, and amine monomers to obtain a mixed solution; adding the cathode material that has undergone plasma treatment to the mixed solution to carry out an in-situ polymerization reaction to form a polymer layer on the surface of the cathode material, thereby obtaining the composite cathode material.

[0047] In the preparation method provided in this application, the aldehyde group in the aldehyde monomer reacts with the amino group in the amine monomer to form a covalent organic framework (COF) with imine bonds. Simultaneously, the borate ester monomer undergoes ring-opening under trace amounts of water to generate a hydroxyl-containing boron ester (ester-B-OH). This intermediate can further undergo dehydration condensation with the hydroxyl groups on the COF backbone to form a stable covalent anchoring link. Furthermore, the two ester-B-OH groups can form a boron-oxygen-boron (BOB) dynamic covalent bridge. These dynamic covalent bonds (including imine bonds, borate ester bonds, and boron-oxygen-boron bonds) can undergo reversible breakage and recombination during cycling, giving the coating layer both self-healing capabilities and structural stability.

[0048] In one embodiment of this application, the borate ester monomer includes at least one of 5,5-dimethyl-1,3,2-dioxoboronylcyclopentane, MIDA cyclobutylboronic acid ester (CAS: 1104637-37-7), and pinacolone ester borate (CAS: 25015-63-8).

[0049] In one embodiment of this application, the borate ester monomer is 5,5-dimethyl-1,3,2-dioxoboropentan, and the chemical structural formula of 5,5-dimethyl-1,3,2-dioxoboropentan is as follows: .

[0050] In one embodiment of this application, the mixture further includes borane, including o-dihydroxyborane. At high potentials, the lattice oxygen on the positive electrode surface oxidizes and releases O2, which induces the dissolution of transition metal ions and further triggers electrolyte decomposition. Borane can act as an oxygen-scavenging agent, endowing the composite positive electrode material provided in this application with the ability to capture O2.

[0051] In one embodiment of this application, the aldehyde monomer includes at least one of terephthalaldehyde (TPA, CAS: 623-27-8), 2,3,5,6-tetrafluoroterephthalaldehyde (TFA, CAS: 3217-47-8), 1,3,5-tricarboxyloylphloroglucinol (Tp, CAS: 34374-88-4), 2,5-diethoxyterephthalaldehyde (CAS: 56766-03-1), 2,5-dipropynoxyterephthalaldehyde (CAS: 1538579-23-5), 2,4-dihydroxy-1,3,5-benzenetrialdehyde (CAS: 58343-11-6), and 2,5-dihydroxyterephthalaldehyde (DHTA, CAS: 1951-36-6).

[0052] In one embodiment of this application, the amine monomer includes at least one of 1,3,5-tris(4-aminophenyl)benzene (TAPB, CAS: 118727-34-7), 1,3,5-tris(4-aminomethylphenyl)benzene, and p-phenylenediamine (CAS: 106-50-3).

[0053] In one embodiment of this application, the mixture further includes an anhydrous polar solvent. Anhydrous polar solvents have a certain polarity, which helps the monomer components to disperse uniformly and contact fully in the system. Furthermore, in practical applications, solvents must be selected that do not undergo side reactions with borate esters or amine monomers, thereby ensuring the smooth progress of the polymerization reaction and the controllability of the product structure. This is beneficial for obtaining composite cathode materials with uniform coating composition and complete functionality.

[0054] In one embodiment of this application, the anhydrous polar solvent includes one or more of anhydrous acetonitrile, anhydrous tetrahydrofuran, anhydrous 2-methyltetrahydrofuran, anhydrous acetone, anhydrous toluene, and xylene, preferably at least one of anhydrous acetonitrile and anhydrous acetone.

[0055] In one embodiment of this application, the amount of borate ester monomer added is 2.0wt% to 4.0wt% of the mass of the cathode material.

[0056] In one embodiment of this application, the amount of borane added is 1.0wt% to 2.0wt% of the mass of the cathode material.

[0057] In one embodiment of this application, the amount of aldehyde monomer added is 3.0wt% to 5.5wt% of the mass of the cathode material.

[0058] In one embodiment of this application, the amount of amine monomer added is 3.5wt% to 6.0wt% of the mass of the cathode material.

[0059] In one embodiment of this application, the amount of anhydrous polar solvent added is 5 to 10 times the mass of the positive electrode material.

[0060] In one embodiment of this application, the mixture further includes at least one of a reaction catalyst and a conductive agent. The reaction catalyst provides free lithium ions during polymerization, promotes efficient imine bond formation, and improves the ionic conductivity of the interfacial layer. The introduction of the conductive agent helps construct effective electron and lithium-ion transport pathways within the coating layer, thereby suppressing the tendency for increased interfacial polarization after coating and ensuring electrode reaction kinetics. When both the reaction catalyst and the conductive agent are introduced simultaneously, their synergistic effect further balances the structural integrity of the coating layer and the interfacial transport performance, which is beneficial for fully utilizing the electrochemical activity of the composite cathode material.

[0061] In one embodiment of this application, the reaction catalyst includes at least one selected from LiTFSI, LiClO4, and LiBOB. In one embodiment of this application, the conductive agent includes at least one of PEDOT-LLTO nanowires, PEDOT:PSS, single-walled carbon nanotubes, and carbon nanofibers.

[0062] In one embodiment of this application, the amount of reaction catalyst added is 0.5wt% to 2.5wt% of the mass of the positive electrode material. In one embodiment of this application, the amount of conductive agent added is 1.0wt% to 4.0wt% of the mass of the positive electrode material.

[0063] In one embodiment of this application, the reaction conditions for the in-situ polymerization reaction are 40°C to 80°C for 1 to 3 hours.

[0064] In one embodiment of this application, the in-situ polymerization reaction needs to be carried out under trace oxygen and water conditions (both H2O and O2 < 1 ppm) to prepare the mixture and polymer layer. The polyboronate, imine bonds, and borane structures in the dynamic covalent system are highly sensitive to moisture and oxygen. Polymerization under oxygen- and anhydrous conditions can effectively avoid the hydrolytic deactivation of borate bonds and the irreversible breakage of imine bonds, while maintaining the oxygen-capturing ability of the borane units. This ensures the structural integrity of the dynamic covalent network in the coating layer and the durability of its gas-capturing function.

[0065] In one embodiment of this application, the in-situ polymerization reaction is carried out under a protective atmosphere.

[0066] In one embodiment of this application, the in-situ polymerization process employs an inert gas displacement operation. This operation can remove byproducts such as alcohols or water generated during the condensation reaction in real time, which helps maintain the equilibrium of the polymerization reaction and allows the resulting coating layer to continue to play a self-healing and interface protection role in subsequent battery cycles.

[0067] In one embodiment of this application, the plasma used in the plasma processing includes oxygen plasma.

[0068] In one embodiment of this application, the radio frequency power of the plasma treatment is 800W~2000W; the working pressure of the cavity is 35Pa~80Pa; and the oxygen flow rate is 15sccm~40sccm.

[0069] In one embodiment of this application, a slurry is obtained after in-situ polymerization and then subjected to microwave treatment. As a preferred embodiment, this application further introduces a microwave treatment step in the preparation of the composite cathode material. It should be noted that microwave treatment is not the only way to form the boron-oxygen-boron (BOB) and COF frameworks; conventional heating can also meet the thermodynamic requirements of the reaction. However, the selective dielectric heating, ultrafast and uniform heating method, and promotion of dynamic bond recombination unique to microwave treatment can more efficiently drive the formation of high-quality BOB crosslinking and COF framework structures. For cathode materials, which have high requirements for the uniformity of the coating structure, defect density, and interface quality, microwave treatment helps to optimize the microstructure of the coating layer at the process level, thereby further improving the overall interfacial stability and electrochemical consistency of the composite cathode material.

[0070] In one embodiment of this application, the microwave treatment reaction conditions are as follows: in an inert gas atmosphere, microwave power is 150W~350W, reaction temperature is 120℃~180℃, and time is 5 minutes~15 minutes.

[0071] In one embodiment of this application, the environmental dew point T during the preparation of the above-mentioned composite cathode material is... d ≤ -40℃.

[0072] According to a third aspect of this application, this application provides a battery comprising the composite positive electrode material as described above, or the composite positive electrode material prepared by the method described above.

[0073] In one embodiment of this application, the battery includes an all-solid-state battery.

[0074] During charging and discharging, gases such as CO2 and O2 are generated on the positive electrode surface due to carbonate decomposition and lattice oxygen release. In sulfide-based solid-state batteries, both gases are significantly destructive: CO2 reacts with the electrolyte and positive electrode interface to generate insulating byproducts such as Li2CO3, blocking ion transport channels and increasing interfacial impedance, thus causing continuous capacity decay; O2 easily oxidizes the sulfide electrolyte under high pressure or high temperature, releasing toxic SO2 gas, accompanied by a large amount of heat, exacerbating the increase in internal pressure and the risk of thermal runaway. Therefore, the combined effect of CO2 and O2 can push solid-state batteries from performance degradation to safety accidents.

[0075] Through the following chemical reaction equations and Figure 1 The composite cathode material provided in this application further illustrates how the polymer layer formed on the surface of the cathode material, utilizing its dynamic covalent network structure and intelligent gas capture mechanism, improves the cycle life and safety performance of the battery. Those skilled in the art should understand that the following specific examples are merely illustrative and are not intended to limit the scope of the invention in any way.

[0076] Specifically, in chemical reaction equation (1), 2,5-dihydroxyterephthalaldehyde (DHTA-CHO) is used as the aldehyde monomer and 1,3,5-tris(4-aminophenyl)benzene is used as the amine monomer (TAPB-NH2) as an example. The two form a covalent organic framework (COF) skeleton containing imine bonds through the reaction of the aldehyde group and the amino group. In addition, in this process, since the amine monomer contains multiple -NH2 structures, the unreacted -NH2 is retained on the COF surface, thereby forming COF-NH2, which provides a reaction basis for capturing CO2. In chemical reaction equation (2), the borate ester monomer reacts with trace water (the trace water mainly comes from the residual water in the cathode material) to open the ring, generating ester-B-OH (after ring opening, the H in the water is connected to ester to form the H-ester-B-OH structure. In order to highlight the reaction site and avoid confusion, the connection of H is omitted here). The ester-B-OH itself can be further dehydrated and crosslinked to form a boron-oxygen-boron (BOB) bond with dynamic reversible characteristics, as shown in chemical reaction equation (3). Furthermore, since DHTA-CHO also contains hydroxyl groups, the resulting COF backbone also retains hydroxyl groups. These hydroxyl groups can undergo dehydration condensation reactions with the aforementioned ester-B-OH intermediate, as shown in chemical reaction equation (4), achieving covalent anchoring between the borate ester group and the COF backbone, thereby introducing dynamic crosslinking sites while increasing the COF chain structure. In addition, since TAPB-NH2 contains 3 amino groups, after the formation of imine bonds consumes some amino groups, a certain amount of free amino groups are still retained in the COF backbone. These amino groups can actively capture CO2 released from the positive electrode surface, reducing the accumulation of harmful gases and the interfacial side reactions they cause from the source. The mechanism of capturing CO2 is shown in chemical reaction equation (5).

[0077]

[0078] Furthermore, the composite cathode material provided in this application also possesses the ability to capture O2. The mechanism of O2 capture in this application is illustrated in chemical reaction equations (6) to (7) using o-dihydroxyborane (B*) as an example. Under conditions containing LiTFSI, trace amounts of water, and a local thermal field, borane can undergo in-situ reduction and cracking to generate trace amounts (ppb level) of BH boron-hydrogen active intermediates. These boron-hydrogen active intermediates have good reducing properties and can effectively consume O2 that may be released near the cathode interface, thereby inhibiting the dissolution of transition metals and electrolyte decomposition caused by oxygen, and further ensuring interface stability.

[0079]

[0080] In addition, trace amounts of water may be generated during the above-mentioned gas capture process. This byproduct can be further transformed through the mechanism shown in chemical reaction equation (8), thereby effectively mitigating its potential impact on interface stability.

[0081]

[0082] In one embodiment of this application, the all-solid-state battery includes a positive electrode sheet, wherein the positive electrode sheet is composed of composite positive electrode material: solid electrolyte A: conductive additive in a mass ratio of 70~90:9~29:1~5.

[0083] In one embodiment of this application, the solid electrolyte A is Li 6-x PS 5-x Cl 1+x Li 6-x PS 5- x ClBr x Li 3+x Ge x P 1-x S4 can be one or two types, where 0 ≤ x ≤ 0.5.

[0084] In one embodiment of this application, the D50 of the solid electrolyte A is 0.5 μm to 1.5 μm.

[0085] In one embodiment of this application, the conductive additive includes VGCF.

[0086] In one embodiment of this application, the all-solid-state battery includes a Li-In negative electrode, wherein the mass fraction of Li is 1% to 5%.

[0087] In one embodiment of this application, the thickness of the negative electrode sheet is 50μm~100μm.

[0088] In one embodiment of this application, the electrolyte sheet in the all-solid-state battery includes a solid electrolyte B.

[0089] In one embodiment of this application, the solid electrolyte B comprises Li 6-x PS 5-x Cl 1+x Li 6-x PS 5- x ClBr x Li 3+x Ge x P 1-x One or two types of S4.

[0090] To further illustrate this application, the following experimental groups are described in detail. Unless otherwise specified, all raw materials used in the following experimental groups of this application are commercially available.

[0091] Example 1 1. Preparation of composite cathode materials In this embodiment, the composite cathode material is prepared according to the following method.

[0092] Commercial single-crystal LiNi with a D50 of 3μm will be used. 0.92 Co 0.07 Mn 0.01 The O2 material (positive electrode material) is spread on a quartz crucible and placed in a plasma activation system. The system parameters are adjusted as follows: radio frequency power to 1200W, cavity working pressure to 50Pa, and oxygen flow rate to 25sccm. After adjusting the parameters, the positive electrode material is processed for 5 minutes and then transferred to a glove box with an Ar atmosphere for later use.

[0093] Based on the mass of the cathode material, 2.8 wt% of 5,5-dimethyl-1,3,2-dioxaborane (boronate monomer), 1.5 wt% of o-dihydroxyborane (borane), 3.5 wt% of terephthalaldehyde (aldehyde monomer), 4 wt% of 1,3,5-tris(4-aminophenyl)phenyl (amine monomer), 1 wt% of PEDOT-LLTO nanowires (conductive agent), and 0.5 wt% of LiTFSI (reaction catalyst) were added. The amount of anhydrous acetonitrile added was 6 times the mass of the cathode material. The above materials were added to a Schlenk tube, placed on a magnetic stirrer, and stirred at 500 rpm for 120 minutes at room temperature (25°C). After stirring, the mixture was evacuated and purged with argon gas three times to remove oxygen, resulting in a mixed solution.

[0094] Move the Schlenk tube into the glove box, pour in the plasma-treated cathode material, quickly seal it, remove it from the glove box, and place it on a heatable magnetic stirrer. React at 600 rpm and 60°C in an oil bath for 1.5 hours.

[0095] After the oil bath, transfer the Schlenk tube back into the glove box. Pour the slurry (containing positive electrode powder and reaction solution) into a microwave-specific quartz tube, seal the quartz tube, and transfer it out of the glove box. Quickly move the quartz tube into the microwave cavity and immediately introduce inert gas at a flow rate of 200 sccm to expel O2 / H2O from the microwave cavity. Adjust the microwave power to 200W, heat to 150℃, hold for 5 to 15 minutes, and allow to cool naturally.

[0096] The naturally cooled powder was placed in anhydrous acetonitrile solvent and centrifuged at 6000 rpm for 5 minutes. This step was repeated twice. The centrifuged powder was then baked in a forced-air drying oven at 120°C for 10 hours to obtain a composite cathode material with a polymer layer coated on the surface of the cathode material. The thickness of the polymer layer was 2.5 nm. In addition, the polymer layer included compound A and compound B. The chemical structure of compound A is shown in formula (V), and compound B includes at least one of the compound structures shown in formulas (VI) to (VIII).

[0097] Formula (5) Formula (VI) Formula (VII) Formula (8) 2. Solid-state battery fabrication The composite cathode material, Li6PS5Cl (D50=0.8μm), and VGCF prepared above were ground in an agate mortar at a mass ratio of 70:29:1 for 30 minutes to obtain a solid cathode composite material. The anode was a Li-In alloy with a thickness of 100μm and a Li mass fraction of 2%, which was cut into a circular piece with a diameter of 10mm. 150mg of Li6PS5Cl (D50=15μm) was weighed and evenly spread in the battery mold, and the electrolyte sheet was formed by pressing at 350MPa and holding the pressure for 3 minutes. The solid cathode composite material was evenly spread on one side of the electrolyte sheet, and the positive electrode sheet was formed by pressing at 200MPa and holding the pressure for 3 minutes. A 10mm diameter Li-In sheet was placed on the other side of the electrolyte sheet, and a copper foil current collector was placed in it. The positive electrode sheet was formed by pressing at 150MPa and holding the pressure for 3 minutes. The mold was tightened and the glove box was removed. The mold was placed in the pressure mold shell and the mold was pressed to 50MPa with a torque wrench to obtain a solid battery.

[0098] Example 2 This embodiment prepares a composite cathode material and a solid-state battery according to the formulation and method provided in Example 1. The difference from Example 1 is that the 5,5-dimethyl-1,3,2-dioxaborane added in this embodiment is 2 wt% of the cathode material, and the thickness of the polymer layer obtained is 2.5 nm. Apart from the above differences, the operation steps for preparing the composite cathode material and solid-state battery in this embodiment are strictly consistent with those in Example 1.

[0099] Example 3 This embodiment prepares a composite cathode material and a solid-state battery using the formulation and method provided in Example 1. The difference from Example 1 is that the added 5,5-dimethyl-1,3,2-dioxaborane, terephthalaldehyde, and 1,3,5-tris(4-aminophenyl)benzene are 4 wt%, 5.5 wt%, and 6 wt% of the cathode mass, respectively, and the thickness of the resulting polymer layer is 5 nm. Apart from the above differences, the operational steps for preparing the composite cathode material and solid-state battery in this embodiment are strictly consistent with those in Example 1.

[0100] Example 4 This embodiment refers to the formulation and method provided in Example 1 to prepare composite cathode materials and solid-state batteries. The difference from Example 1 is that in this embodiment, 5,5-dimethyl-1,3,2-dioxaborane is added at 1 wt% of the cathode material mass when preparing the composite cathode material, and the thickness of the polymer layer formed is 1.3 nm. Apart from the above differences, the operation steps for preparing composite cathode materials and solid-state batteries in this embodiment are strictly consistent with those in Example 1.

[0101] Example 5 This embodiment refers to the formulation and method provided in Example 1 to prepare composite cathode materials and solid-state batteries. The difference from Example 1 is that in this embodiment, when preparing composite cathode materials, 5,5-dimethyl-1,3,2-dioxaborane, terephthalaldehyde, and 1,3,5-tris(4-aminophenyl)benzene are 6 wt%, 6 wt%, and 8 wt% of the cathode mass, respectively, and the thickness of the polymer layer formed is 6 nm. Apart from the above differences, the operation steps for preparing composite cathode materials and solid-state batteries in this embodiment are strictly consistent with those in Example 1.

[0102] Example 6 This embodiment refers to the formulation and method provided in Example 1 to prepare composite cathode materials and solid-state batteries. The difference from Example 1 is that, in preparing the composite cathode material, an equal mass fraction of 2,5-dihydroxyterephthalaldehyde is used instead of terephthalaldehyde. Apart from the above differences, the operational steps for preparing the composite cathode material and solid-state battery in this embodiment are strictly consistent with those in Example 1. The compound A obtained in this embodiment includes the compound shown in formula (IX).

[0103] Formula (9) Example 7 This embodiment refers to the formula and method provided in Embodiment 1 to prepare composite cathode materials and solid-state batteries. The difference from Embodiment 1 is that no conductive agent is added when preparing composite cathode materials in this embodiment. Apart from the above differences, the operation steps for preparing composite cathode materials and solid-state batteries in this embodiment are strictly consistent with those in Embodiment 1.

[0104] Example 8 This embodiment refers to the formulation and method provided in Example 1 to prepare composite cathode materials and solid-state batteries. The difference from Example 1 is that no reaction catalyst is added when preparing composite cathode materials in this embodiment. Apart from the above differences, the operation steps for preparing composite cathode materials and solid-state batteries in this embodiment are strictly consistent with those in Example 1.

[0105] Example 9 This embodiment refers to the formulation and method provided in Example 1 to prepare composite cathode materials and solid-state batteries. The difference from Example 1 is that borane is not added when preparing composite cathode materials in this embodiment. Apart from the above differences, the operation steps for preparing composite cathode materials and solid-state batteries in this embodiment are strictly consistent with those in Example 1.

[0106] Comparative Example 1 This comparative example prepares a solid-state battery using the formulation and method provided in Example 1. The difference from Example 1 is that this comparative example uses an equal mass fraction of unmodified cathode material (LiNi) when preparing the solid cathode composite material. 0.92 Co 0.07 Mn 0.01 Except for the differences mentioned above, the operation steps for preparing solid-state batteries in this comparative example are strictly consistent with those in Example 1, except that O2 is used instead of composite cathode materials.

[0107] Comparative Example 2 This comparative example prepares composite cathode materials and solid-state batteries according to the formulation and method provided in Example 1. The difference between this comparative example and Example 1 is that no amine monomers and borate esters are added during the preparation of the composite cathode material. Apart from the above differences, the operation steps for preparing composite cathode materials and solid-state batteries in this comparative example are strictly consistent with those in Example 1.

[0108] Comparative Example 3 This comparative example prepares a composite cathode material and a solid-state battery using the formulation and method provided in Example 1. The difference from Example 1 is that no aldehyde monomer is added during the preparation of the composite cathode material in this comparative example. Apart from the above differences, the operational steps for preparing the composite cathode material and solid-state battery in this comparative example are strictly consistent with those in Example 1.

[0109] Test Example 1 1. Test Object The solid-state batteries prepared in Examples 1-7 and Comparative Examples 1-3 were used as test subjects.

[0110] 2. Testing Methods Discharge specific capacity / first-efficiency test method: Place the test object on the Xinwei Battery Testing Cabinet CTE-4064 and charge it to 3.7V at a constant current of 0.1C. Collect the test data to obtain the charge specific capacity C0 of the solid-state battery. After standing for 15 minutes, discharge it to 1.9V at 0.1C and collect the test data to obtain the discharge specific capacity C1 of the pouch battery. Calculate the 0.1C first-time coulombic efficiency according to the following formula: 0.1C first-time coulombic efficiency = C1 / C0*100%. The discharge capacity test methods for 0.3C, 0.5C, and 1C are the same as the above charge and discharge methods, only the charge and discharge rates are different (corresponding to 0.3C, 0.5C, and 1C, respectively).

[0111] Capacity retention rate test method: Place the test object on the Xinwei Battery Testing Cabinet CTE-4064. Charge the battery to 3.7V using a constant current of 0.1C, let it stand for 15 minutes, then discharge it to 1.9V using 0.1C. Repeat this process twice. Then charge it to 3.7V using a constant current of 0.5C, and then charge it to 3.7V using a constant voltage until the current ≤ 0.05C. Collect the test data to obtain the charging specific capacity C2 of the soft-pack battery. After standing for 15 minutes, discharge it to 1.9V using 0.5C. Collect the test data to obtain the discharging specific capacity C3 of the soft-pack battery. Let it stand for 15 minutes. Repeat this process n times to obtain the discharging specific capacity C. n+2 Then, the capacity retention rate after repeating 0.5C n times is C. n+2 / C2*100%.

[0112] Gas detection procedure: The test object is placed in a sealed cell, and high-purity Ar gas is purged at a constant flow rate of 1 mL / min while recording the background; subsequently, it is charged to 3.7V at 0.1C, and the interface gas is carried out in real time by the carrier gas. After removing condensable substances in a 40℃ cold trap, the sample enters a quadrupole mass spectrometer through a PTFE membrane. The mass spectrometer performs millisecond-level scans of signals at m / z 44, 64, and 32 to obtain ion current curves that vary with voltage. The sample is then calibrated with an external standard using a standard gas. Combined with the carrier gas flow rate and the amount of reaction charge, the molar amounts and Faraday efficiencies of byproduct gases such as CO2, SO2, and O2 are quantified online. After the test is completed, the sample is purged back to baseline, and the cell is disassembled and cleaned.

[0113] 3. Test Results and Analysis The test results for this example are shown in Tables 1 and 2, respectively. From the test results of the examples and comparative examples, the composite cathode material provided in this application shows significant improvements in both electrochemical performance and interfacial stability. Compared to the unmodified Comparative Example 1, each example shows improvements in first-cycle coulombic efficiency, rate performance, and cycle capacity retention, while effectively suppressing the generation of CO2, O2, and SO2, indicating that the polymer layer can reduce the accumulation of harmful gases and their associated side reactions at the source. Comparative Example 2, lacking amine monomers and catalysts, could not form a complete imine framework and gas trapping sites, resulting in a significantly lower capacity retention and still detected gas release, further confirming the crucial role of imine bonds and amino groups in gas trapping and self-repair. Similarly, Comparative Example 3, lacking aldehyde monomers, could not form imine bonds and a COF framework structure, leading to a decrease in cycle performance.

[0114] As demonstrated in Examples 1-5, the thickness of the polymer layer affects the electrochemical performance of the solid-state battery. In Example 4, due to the low amount of borate ester monomer added and a thinner coating layer, although the initial efficiency was acceptable, the capacity retention decreased rapidly in the later stages of cycling, and O2 and SO2 were observed. This indicates that an excessively thin coating layer and fewer boron-oxygen-boron (BOB) bonds are insufficient to continuously block interfacial side reactions and capture oxygen. Conversely, when the coating layer is too thick (as in Example 5), the rate performance decreases slightly, but the cycle stability remains good. In contrast, Examples 1-3, within a suitable thickness range, all maintained high capacity retention and produced no gas, with Example 1 exhibiting the most balanced overall performance.

[0115] In addition, compared with Example 1, Example 6 introduces an aldehyde monomer containing hydroxyl groups, and introduces borate ester bonds (COB) into the structure of compound A in the polymer layer, which can further improve the self-healing performance of the coating layer, thereby improving the cycle performance of the solid-state battery.

[0116] In Example 7, without the addition of a conductive agent, the rate performance was lower than that of Example 1, indicating that the introduction of the conductive agent helps to alleviate the tendency of increased polarization after coating and ensures rapid ion / electron transport. In Example 8, without the addition of a reaction catalyst, the performance declined compared to Example 1, indicating that the introduction of a reaction catalyst helps to provide free Li + This promotes efficient condensation of imine bonds and improves the ionic conductivity of the interfacial layer, while reducing the polarization of the coating layer. Furthermore, as illustrated in Example 9, the introduction of borane helps optimize the active gas capture mechanism in the polymer layer, further capturing any potential O2.

[0117] Overall, the polymer layer provided in this application can synergistically perform gas trapping, self-healing, and lithium-conducting electronic functions, thereby effectively improving the cycle life and safety performance of solid-state batteries.

[0118] Table 1. Electrochemical performance of Examples 1-7 and Comparative Examples 1-2

[0119] Table 2. Gas production in the first cycle of Examples 1-7 and Comparative Examples 1-4

[0120] The above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.

Claims

1. A composite cathode material, characterized in that, The composite cathode material includes a cathode material and a polymer layer covering its surface, wherein the polymer layer includes compound A containing both imine bonds and amino groups.

2. The composite cathode material as described in claim 1, characterized in that, Compound A also includes borate ester bonds.

3. The composite cathode material as described in claim 1 or 2, characterized in that: The compound A is a compound as shown in formula (I); Formula (1) Wherein, A1 is selected from substituted or unsubstituted phenyl groups, and when the phenyl group is substituted, the substituent is selected from at least one of C1-4 alkyl, phenyl, aminophenyl, hydroxyl, and halogen; A2 is selected from substituted or unsubstituted phenyl groups, and when the phenyl group is substituted, the substituent is selected from at least one of halogen, hydroxyl, C1-4 alkyl or haloalkyl, C1-4 alkenyl, C1-4 alkynyl, and C1-4 aldehyde. R1, R2, R3, R4, and R5 are each independently selected from one of the following groups: hydrogen atom, amino group, hydroxyl group, aldehyde group, and group shown in formula (II), and at least one of R1 and R2 contains an amino group; Formula (II) In the groups shown in formula (ii), Indicates a linking bond; R6 and R7 are each independently selected from one of substituted or unsubstituted C3-6 cycloalkyl, substituted or unsubstituted C1-8 alkoxy, or substituted or unsubstituted C1-8 alkyl. When the cycloalkyl, alkoxy, or alkyl is substituted, the substituent is each independently selected from at least one of carbonyl, ester, or C1-3 alkyl. R8 and R9 are each independently selected from one of hydrogen atom or substituted or unsubstituted C1-8 alkyl.

4. The composite cathode material as described in claim 1 or 2, characterized in that: The polymer layer also includes compound B containing boron-oxygen-boron bonds, the structural formula of which is shown in formula (iii); Formula (3) Among them, R 10 R 11 R 12 R 13 Each substituent is independently selected from one of substituted or unsubstituted C3-6 cycloalkyl, substituted or unsubstituted C1-8 alkoxy, or substituted or unsubstituted C1-8 alkyl; when the cycloalkyl, alkoxy, or alkyl is substituted, the substituent is independently selected from at least one of carbonyl, ester, or C1-3 alkyl.

5. The composite cathode material as described in claim 1, characterized in that, The cathode material includes a nickel-containing material, the chemical formula of which is LiNi. x Co y M 1-x-y O2; wherein M is one or more of Li, Na, B, Mg, Al, Ni, Fe, Mn, K, Ca, Co, V, Cr, Cu, Zn, Zr, Nb, Sr, Sn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; 0.8 <x<1,0<y<0.2,0<z<0.2; And / or, the D50 of the positive electrode material is 3μm~6μm.

6. A method for preparing the composite cathode material as described in any one of claims 1 to 5, characterized in that, The method includes the following steps: mixing at least borate ester monomers, aldehyde monomers, and amine monomers to obtain a mixture; adding the plasma-treated cathode material to the mixture to perform an in-situ polymerization reaction to form a polymer layer on the surface of the cathode material, thereby obtaining the composite cathode material.

7. The method as described in claim 6, characterized in that, The in-situ polymerization reaction satisfies at least one of the following conditions: (a) The borate ester monomer comprises at least one of 5,5-dimethyl-1,3,2-dioxoboronylcyclopentane, MIDA cyclobutylboronic acid ester, and pinacol ester borate; (b) The aldehyde monomer comprises at least one of terephthalaldehyde, 2,3,5,6-tetrafluoroterephthalaldehyde, 1,3,5-tricarboxyloylphloroglucinol, 2,5-diethoxyterephthalaldehyde, 2,5-dipropynoxyterephthalaldehyde, 2,4-dihydroxy-1,3,5-benzenetrialdehyde, and 2,5-dihydroxyterephthalaldehyde; (c) The amine monomer includes at least one of 1,3,5-tris(4-aminophenyl)benzene, 1,3,5-tris(4-aminomethylphenyl)benzene, and p-phenylenediamine; (d) The amount of the borate ester monomer added is 2.0 wt% to 4.0 wt% of the mass of the cathode material; (e) The amount of the aldehyde monomer added is 3.0 wt% to 5.5 wt% of the mass of the cathode material; (f) The amount of the amine monomer added is 3.5 wt% to 6.0 wt% of the mass of the cathode material; (g) The mixture further includes at least one of a reaction catalyst and a conductive agent; The reaction catalyst includes at least one of LiTFSI, LiClO4, and LiBOB; the conductive agent includes at least one of PEDOT-LLTO nanowires, PEDOT:PSS, single-walled carbon nanotubes, and carbon nanofibers; and / or, the amount of the reaction catalyst added is 0.5wt% to 2.5wt% of the mass of the cathode material, and the amount of the conductive agent added is 1.0wt% to 4.0wt% of the mass of the cathode material. (h) The reaction conditions for the in-situ polymerization reaction are 1 to 3 hours at 40°C to 80°C.

8. The method as described in claim 6, characterized in that, The plasma used in the plasma treatment includes oxygen plasma.

9. The method as described in claim 6, characterized in that, After the in-situ polymerization reaction, a slurry is obtained, and the slurry is subjected to microwave treatment. The microwave treatment reaction conditions are: in an inert gas atmosphere, microwave power of 150W~350W, reaction temperature of 120℃~180℃, and time of 5 minutes~15 minutes.

10. A battery, characterized in that, The battery includes the composite cathode material as described in any one of claims 1 to 5, or the composite cathode material prepared by the method described in any one of claims 6 to 9.